The Cold War in Asia : the battle for hearts and minds - Zheng, Yangwen; Liu, Hong, 1959 November 1-; Szonyi, Michael (Brill, 2010)
This volume argues that attention to what has been conventionally considered the periphery is essential to a full understanding of the global Cold War. This volume also argues for a shift in focus from diplomacy and high politics alone towards research into the culture of the Cold War era and its public diplomacy.